ARMENIAN INSCRIPTIONS FROM THE ST. PANTELEIMON CHURCH IN HALYCH - MNATSAKANYAN, Piruz (Halych. Scientific work collection, 2017)
The article is devoted to three Armenian inscriptions that remained on the walls of the St. Panteleimon church in Halych. The study examined several references and readings of these inscriptions in the Armenian historiography, and versions of their appearance on the walls of the temple.